Ligand functionalized copper nanoclusters for versatile applications in catalysis, sensing, bioimaging, and optoelectronics. (20th September 2019) - Shahsavari, Shayan; Hadian-Ghazvini, Samaneh; Hooriabad Saboor, Fahimeh; Menbari Oskouie, Iman; Hasany, Masoud; Simchi, Abdolreza; Rogach, Andrey L.
Abstract : Chemically synthesized copper nanoclusters show colour-tunable emission and can be applied in catalysis, sensing, bioimaging, theranostics, and optoelectronics. Abstract : Copper nanoclusters (Cu NCs) have emerged as a valuable member of the family of ligand-protected few-atomic metal nanoparticles and show fascinating properties of color-controlled light emission, combined with the advantages of versatile solution-based chemical synthesis at low cost. Synthetic methods of Cu NCs using various types of functional ligands and scaffolds allow tuning their emission wavelength and improving their environmental stability. Depending on the method of preparation and the ligands used, Cu NCs have already been applied for a wide variety of applications in catalysis, sensing, bioimaging, theranostics, and optoelectronics. This review highlights the potential of Cu NCs and links synthetic procedures and functionalization with different ligands with their properties and applications.